The level of awareness and production of English lexical stress among English language teacher trainees in Malaysia - Adnan, Ernie; Pillai, Stefanie; Chiew, Poh Shin (Universitas Pendidikan Indonesia, 2019)
The realisation of lexical stress among Malaysian speakers of English is likely to be different from other varieties of English. In spite of this, there is a preference for a native pronunciation model in the teaching of English in Malaysia. In relation to this issue, this paper focuses on lexical stress among a group of Teaching of English as a Second Language teacher trainees. The objectives of this paper are to assess the overall level of awareness of lexical stress among them, to examine their production of lexical stress, and to determine the link between their level of awareness and production. The method used to elicit data for the first objective was a Lexical Stress Awareness Test (LSAT), completed by 104 teacher trainees. Data for the second objective were obtained by recording the trainees reading sentences containing test words. The findings from the LSAT indicate that most of the trainees have an intermediate level of awareness of English lexical stress. They were generally unable to describe the characteristics of a stressed syllable. In addition, the findings from the acoustic analysis of the recordings suggest that they did not have a systematic pattern of stressing syllables with the main correlate of stress being vowel lengthening. In contrast, most of them chose ‘higher pitch’ as the characteristic of a stressed syllable. Hence, there is an inconsistency between their awareness and production of lexical stress in English. We discuss the implications of these findings in relation to the teaching of pronunciation in the classroom and the effect of lexical stress placement on intelligibility. Our general conclusion is that more attention needs to be given in teacher education to how lexical stress is used in English, and also to the characteristics of stress in the Malaysian variety of English.